Acoustic Detection, Behavior, and Habitat Use of Deep-Diving Odontocetes - Johnson, Mark; Tyack, Peter; Aguilar, Natacha; Brito, Alberto; Madsen, Peter (2008)
Passive acoustic monitoring is a key enabling technology in mitigating the effects of Naval activities on sound-sensitive cetaceans. The goals of this project are to obtain and disseminate critical information needed for the design of acoustic monitoring systems. Prepared in cooperation with University of La Laguna, Tenerife, Spain; and University of Aarhus, Aarhus, Denmark. The original document contains color images.